Annual dynamics of a macroalgal rocky community in the Gulf of Pozzuoli (Naples, Italy): exploring variations across ecological, structural and functional traits of dominant populations - Ermenegilda Vitale; Rosa Donadio; Claudia Manfredonia; Lorenzo Saviano; Giovanni Libralato; Simonetta Fraschetti; Carmen Arena (Environmental Research, 2026)

Exploring the multiple functions of polyphenols in Mediterranean macroalgae: insights, gaps, and future directions from a systematic review - Ermenegilda Vitale; Rosa Donadio; Simonetta Fraschetti; Carmen Arena (Marine Environmental Research, 2026)

Unlocking the potential of other effective area-based conservation measures (OECMs) for achieving conservation targets: A global scoping review - Dimitra Petza; Eva Amorim; Emna Ben Lamine; Francesco Colloca; Esther Dominguez Crisóstomo; Erika Fabbrizzi; Simonetta Fraschetti; Ibon Galparsoro; Sylvaine Giakoumi; Maren Kruse; Vanessa Stelzenmüller; Stelios Katsanevakis (Ambio, 2026)
Other Effective Area-based Conservation Measures (OECMs), introduced by the Convention on Biological Diversity (CBD), refer to areas outside formal protected-area networks that deliver effective and enduring in situ biodiversity conservation. This scoping review systematically examined global approaches to identifying and evaluating potential OECMs. Analysing 99 studies covering 694 case studies and 237 000 potential sites, we found that potential OECMs are widespread, particularly in Asia and terrestrial environments, with most initiatives led by the environmental sector. Assessments relied largely on qualitative expert knowledge, with limited application of analytical methods. Although CBD criteria were commonly applied, contributions of related to ecosystem services and socio-cultural values were often overlooked. Effectiveness evaluations showed considerable uncertainty, with over one-third of case studies reporting inadequate evidence of conservation outcomes. The review emphasises the need for standardised assessment methodologies, improved decision-support tools, and socio-cultural integration to enhance OECM recognition, particularly under the 30 × 30 conservation biodiversity target.

Technologies for marine biodiversity monitoring and mapping: A systematic review - Gennaro Ucciero; Marzia Cianflone; Andrea Capuozzo; Francesco Wanderlingh; Andrea Tiranti; Francesca Acampa; Giovanni Indiveri; Vincenzo Lippiello; Simonetta Fraschetti (Marine Pollution Bulletin, 2026)

Vegetated habitats as natural macrolitter traps in an Apulian site along the Southeastern Adriatic Coast: Insights from the Ericaria crinita macroalgal canopy - Lucia Rizzo; Andrea Picciolo; Simonetta Fraschetti (Marine Pollution Bulletin, 2026)

Resilience of the macroalgae Gongolaria barbata under ocean acidification: physiological responses and restoration perspective - Ilaria D'Aniello; Maria Nardiello; Carmen Arena; Denis Badocco; Alberto Barausse; Alberto Colletti; Roberto Danovaro; Erika Fabbrizzi; Marta Formentin; Simonetta Fraschetti; Folco Giomi; Valerio Matozzo; et al. (Marine Environmental Research, 2026)

Habitat suitability model for predicting the occurrence of scleractinian cold-water corals in the Gulf of Naples (Tyrrhenian Sea): A tool for restoration planning and governance of deep-sea ecosystems - Fabio Di Giovanna; Giorgio Castellan; Michela Angiolillo; Vincenzo Botte; Simonetta Fraschetti; Valentina Grande; Daniele Iudicone; Florian Kokoszka; Paolo Montagna; Mariacristina Prampolini; Giorgio Simone; Marco Taviani; et al. (Marine Environmental Research, 2026)

Influence of red gorgonian (Paramuricea clavata) forests on coralligenous community structure across different regions, seasons, thermal environment, and water trophic state - La Manna Gabriella; Bolinesi Francesco; Bosch-Belmar Maria del Mar; Colletti Alberto; Di Marino Claudio; Fabietti Ylenia; Fraschetti Simonetta; Licciardi Luca; Mancuso Francesco Paolo; Mangoni Olga; Morello Giuseppe; Musumeci Simone Maria Santo; et al. (Coral Reefs, 2026)

Updated distribution mapping of Posidonia oceanica meadows, coralligenous assemblages and marine caves in the Mediterranean Sea: implications for conservation and restoration - VASILIS GEROVASILEIOU; ANTONIO SÁNCHEZ-ESPINOSA; DAVID RODRÍGUEZ-RODRÍGUEZ; SIMONETTA FRASCHETTI; INÉS MAZARRASA; CYRINE BOUAFIF; ATEF OUERGHI; DANIA ABDUL MALAK (Mediterranean Marine Science, 2026)
Marine habitats in the Mediterranean Sea play a vital role in supporting biodiversity, ecosystem functioning and services, and climate resilience. However, they are facing escalating threats from anthropogenic pressures. This study, coordinated and financially supported by the Specially Protected Areas Regional Activity Centre (SPA/RAC) under the Barcelona Convention, presents an updated, harmonized assessment of the distribution and protection status of three iconic benthic habitats: Posidonia oceanica meadows, coralligenous assemblages, and marine caves. A standardized methodology was applied to compile, review, harmonize, and aggregate fine-scale data from regional databases, National Focal Points (NFPs), expert networks, and online repositories. Posidonia oceanica meadows were mapped over 22,379 km² across 15 Mediterranean countries, with 95% within territorial waters and 37% in Marine Protected Areas (MPAs). Coralligenous assemblages and maërl beds covered 2,889.5 km² in 13 countries, in line with previous modelling estimates, with 67.1% located within MPAs, particularly in the central and western regions. Approximately 3,000 marine caves were identified across 15 countries, representing the first country-level spatial inventory of this habitat. Nearly 69% of known caves are located in MPAs, although lacking specific conservation measures. Despite significant progress, notable limitations remain. Data quality and availability are uneven across regions, and inconsistencies in classification, spatial resolution, and ecological descriptors – especially for coralligenous assemblages and marine cave typologies – limit detailed habitat representation. This study highlights persistent knowledge gaps in parts of North Africa, the Eastern Mediterranean, and non-EU coastal states, and provides a robust baseline for conservation planning and supports regional monitoring efforts under the Barcelona Convention. Future priorities include addressing data gaps, standardizing classification systems, prioritizing sites for conservation and restoration to strengthen marine habitat protection and recovery and enhance the ecological effectiveness of MPAs.

CoDeMap: a classification scheme for benthic habitats from the coast to the deep sea in the Mediterranean and Black Sea - Valentina Grande; Lorenzo Angeletti; Mariacristina Prampolini; Giorgio Castellan; Giacomo Dalla Valle; Simonetta Fraschetti; Daniela Basso; Dimitar Berov; Valentina A. Bracchi; Frine Cardone; Giovanni Chimienti; Annalisa Falace; et al. (Frontiers in Marine Science, 2025)
The spatial representation of benthic habitats is essential across various applications, such as biodiversity monitoring, ecosystem management and conservation, and maritime spatial planning. In this context, classification schemes provide a universally understandable framework to characterize and chart the seafloor. This work introduces the Coast to Deep Mapping (CoDeMap) classification scheme for benthic habitats from the coast to the deep-sea environments. It consists of three main components (Morphology, Substrate and Biology) and it is conceived as a practical tool for users from various backgrounds who need to organize and interpret marine observational data, as well as characterize and map seafloors. While primarily developed for the Mediterranean Sea and the Black Sea, CoDeMap serves as a foundational framework that can be adapted to address any current or future similar request worldwide.

Small-scale fishery as a driver of habitat loss in marine protected areas - Chiara Silvestrini; Alessandro Ciccolella; Paolo D'Ambrosio; Francesco de Franco; Luciana Muscogiuri; Simonetta Fraschetti (Journal of Environmental Management, 2025)

Posidonia oceanica leaf bleaching: does it affect the plant photoprotective mechanisms? - Patrizia Stipcich; Carmen Arena; Giulia Ceccherelli; Rosa Donadio; Carlos Jimenez; Vasilis Resaikos; Ermenegilda Vitale; Simonetta Fraschetti (Environmental Research, 2025)

Not only corals: seagrass bleaching in the eastern Mediterranean - Patrizia Stipcich; Carmen Arena; Giulia Ceccherelli; Rosa Donadio; Carlos Jimenez; Gabriella La Manna; Vasilis Resaikos; Ermenegilda Vitale; Simonetta Fraschetti (Science of The Total Environment, 2025)

Assessing the resilience of the coralline macroalga Ellisolandia elongata in response to a prolonged low tide - Rosa Donadio; Ermenegilda Vitale; Giulia Costanzo; Luca Licciardi; Erika Fabbrizzi; Simonetta Fraschetti; Carmen Arena (Environmental Research, 2025)

Advances in systematic conservation planning to meet global biodiversity goals - Sylvaine Giakoumi; Anthony J. Richardson; Aggeliki Doxa; Stefano Moro; Marco Andrello; Jeffrey O. Hanson; Virgilio Hermoso; Tessa Mazor; Jennifer McGowan; Heini Kujala; Elizabeth Law; Jorge G. Álvarez-Romero; et al. (Trends in Ecology & Evolution, 2025)

Subtidal benthic assemblages in a mediterranean bank along a depth gradient: Conservation perspectives of a vulnerable marine ecosystem - Lucia Rizzo; Andrea Picciolo; Giulio Tarantino; Luciana Muscogiuri; Simonetta Fraschetti; Antonio Terlizzi; Paolo D'Ambrosio (Ocean & Coastal Management, 2025)

Occurrence of Phyllariopsis brevipes (C. Agardh) E.C. Henry & G.R. South 1987 in the Gulf of Naples - Alberto Colletti; Antonia Chiarore; Sara De Benedictis; Erika Fabbrizzi; Giulio Franzitta; Luca Licciardi; Simone Musumeci; João Neiva; Chiara Silvestrini; Simonetta Fraschetti (Marine Ecology, 2024)
The first record of the kelp species Phyllariopsis brevipes in the Campania Region (Tyrrhenian Sea, South Italy) is here reported. The species has been observed in October 2021 in four sites along Sorrento Peninsula and Capri Island coast during scuba diving surveys. P. brevipes grew on living thalli of crustose coralline algae from 32 up to 55 m depth, occasionally forming dense aggregations with a maximum cover of about 0.2 m 2 . The DNA barcoding analysis on the basis of the cox1 gene supported the identification, with 98.36% of similarity between the sample collected in this study (NCBI accession number: PP622796 ) and a sequence obtained from a specimen from Provence, Mediterranean France (NCBI accession number: GQ368264 ). The study area can be considered a stepping stone for the species dispersion. The occurrence of P. brevipes can be related to upwelling and good water quality and the monitoring of its health status might be a sentinel of environmental changes.

How the seagrass Posidonia oceanica flowering will benefit from climate change - Patrizia Stipcich; Ivan Guala; Gabriella La Manna; Mariangela Moro Merella; Arianna Pansini; Riccardo Vargiu; Simonetta Fraschetti; Giulia Ceccherelli (Marine Pollution Bulletin, 2024)

Habitat loss and small‐scale fishery: A controversial issue - Chiara Silvestrini; Alberto Colletti; Antonio Di Franco; Francesco Colloca; Giacomo Milisenda; Serena Zampardi; Maria Cristina Mangano; Giorgio Aglieri; Marco Ranù; Gianluca Liguori; Roberto Danovaro; Federica Foglini; et al. (Marine Ecology, 2024)
Fishery is one of the most impacting human activities and is responsible for habitat loss in marine systems. While the effects of large‐scale fisheries have been largely investigated, impacts of small‐scale fisheries (SSF) on seafloor integrity are more often assumed than quantitatively investigated. We carried out a literature review at global scale, resulting in 19 studies with quantitative data on sessile benthic bycatch and only one documenting habitat loss driven by SSF. We also conducted a fine‐scale assessment within a Mediterranean partially protected area (PPA). Results showed that 513 m 2 of the Posidonia oceanica meadow are removed annually by local SSF within the PPA, considering bycatch, fishing effort, and shoot density. Knowledge on fishing effort and fine‐scale mapping is critical to assess habitat loss, suggesting the need for specific recommendations for eco‐sustainable local fisheries.

Top predator status and trends: ecological implications, monitoring and mitigation strategies to promote ecosystem-based management - Caterina Maria Fortuna; Tomaso Fortibuoni; Juan Bueno-Pardo; Marta Coll; Anita Franco; Joan Giménez; Yolanda Stranga; Myron A. Peck; Cristina Claver; Sophie Brasseur; Elena Fernández-Corredor; Simonetta Fraschetti; et al. (Frontiers in Marine Science, 2024)
The conservation and management of marine ecosystems hinge on a comprehensive understanding of the status and trends of top predators. This review delves into the ecological significance of marine top predators, examining their roles in maintaining ecosystem stability and functioning through an integrated analysis of current scientific literature. We first assess the efficacy of various monitoring methods, ranging from traditional field observations to cutting-edge technologies like satellite tracking and environmental DNA (eDNA) analysis and evaluating their strengths and limitations in terms of accuracy, spatial coverage, and cost-effectiveness, providing resource managers with essential insights for informed decision-making. Then, by synthesizing data from diverse marine ecosystems, this study offers a comprehensive overview of the trends affecting top predator populations worldwide. We explore the multifaceted impacts of human activities, climate change, and habitat degradation on the abundance and distribution of these key species. In doing so, we shed light on the broader implications of declining top predator populations, such as trophic cascades and altered community structures. Following a thorough assessment of successful strategies for reversing the decline of top predators, a compilation of recommendations is presented, encompassing effective governance interventions. A crucial aspect of effective ecosystem-based management is the implementation of robust monitoring strategies. Mitigation measures are imperative to reverse the adverse impacts on marine top predators. We present a comprehensive array of mitigation options based on successful case studies. These include the establishment of marine protected areas, the enforcement of fisheries regulations, and the promotion of sustainable fishing practices. We deepen the synergies between these strategies and their potential to mitigate human-induced stressors on top predator populations to safeguard their pivotal role in maintaining marine ecosystem structure and function. By examining marine top predators’ ecological significance, analyzing population trends, discussing monitoring techniques, and outlining effective mitigation strategies, we provide a comprehensive resource for researchers, policymakers, and stakeholders engaged in fostering ecosystem-based management approaches. We conclude that integrating these insights into current management frameworks will be essential to safeguard both top predators and the broader marine environment for future generations.

2bRAD reveals fine-scale genetic structuring among populations within the Mediterranean zoanthid Parazoanthus axinellae (Schmidt, 1862) - Marko Terzin; Adriana Villamor; Lorenzo Marincich; Kenan Matterson; Maria Grazia Paletta; Valentina Bertuccio; Giorgio Bavestrello; Lisandro Benedetti Cecchi; Elisa Boscari; Carlo Cerrano; Giovanni Chimienti; Leonardo Congiu; et al. (Coral Reefs, 2024)
The zoanthid Parazoanthus axinellae (Schmidt, 1862) is a widespread coral species in the Mediterranean coralligenous assemblages where two morphotypes are found: Slender and Stocky, differing in size, color, and preferred substrate. Due to these marked differences, Slender and Stocky morphotypes were hypothesized to be two species. Here, we used 2bRAD to obtain genome‐wide genotyped single nucleotide polymorphisms (SNPs) to investigate the genetic differentiation between Slender and Stocky morphs, as well as their population structure. A total of 101 specimens of P. axinellae were sampled and genotyped from eight locations along the Italian coastline. In four locations, samples of the two morphotypes were collected in sympatry. 2bRAD genome-wide SNPs were used to assess the genetic divergence between the two morphotypes (1319 SNPs), and population connectivity patterns within Slender (1926 SNPs) and Stocky (1871 SNPs) morphotypes. Marked and consistent differentiation was detected between Slender and Stocky morphotypes. The widely distributed Slender morphotype showed higher population mixing patterns, while populations of the Stocky morphotype exhibited a stronger genetic structure at a regional scale. The strong genetic differentiation observed between P. axinellae Slender and Stocky morphotypes provides additional evidence that these morphs could be attributed to different species, although further morphological and ecological studies are required to validate this hypothesis. Our study highlights the importance of resolving phylogenetic and taxonomic disparities within taxonomically problematic groups, such as the P. axinellae species complex, when performing genetic connectivity studies for management and conservation purposes. Graphical Abstract Schematic overview of the main genetic structuring patterns observed in this study. Coral polyps were colored to intuitively associate the reader to Parazoanthus axinellae morphotypes, with orange tones being attributed to the Stocky morphotype, and yellow tones to the Slender morphotype. Bidirectional arrows represent gene flow between coral individuals, with the number and thickness of arrows corresponding to the intensity of gene flow rates. The red dashed line represents the potential reproductive isolation between Slender and Stocky morphs

Poor online information on European marine protected areas impairs public participation under the Aarhus Convention - Valentina Rossi; Carlo Pipitone; Katherine L. Yates; Fabio Badalamenti; Giovanni D’Anna; Cristina Pita; Fátima L. Alves; Jesús E. Argente-García; Jelena Basta; Joachim Claudet; Karsten Dahl; Simonetta Fraschetti; et al. (Marine Policy, 2024)

Canopy-forming macroalgae can adapt to marine heatwaves - Erika Fabbrizzi; Marco Munari; Simonetta Fraschetti; Carmen Arena; Antonia Chiarore; Antonio Cannavacciuolo; Alberto Colletti; Giulia Costanzo; Ana Soler-Fajardo; Matteo Nannini; Beatrice Savinelli; Chiara Silvestrini; et al. (Environmental Research, 2023)

Distribution, health and threats to Mediterranean macroalgal forests: defining the baselines for their conservation and restoration - Jana Verdura; Lluc Rehues; Luisa Mangialajo; Simonetta Fraschetti; Zahira Belattmania; Silvia Bianchelli; Aurélie Blanfuné; Brahim Sabour; Antonia Chiarore; Roberto Danovaro; Erika Fabbrizzi; Sylvaine Giakoumi; et al. (Frontiers in Marine Science, 2023)
The worldwide decline of macroalgal forests is raising major concerns for the potentially negative consequences on biodiversity and ecosystem functions, pushing for the definition of specific conservation and restoration measures. Protecting and restoring these habitats requires detailed information on their distribution, ecological status, and drivers of decline. Here, we provide the most updated available information on the distribution of Mediterranean Cystoseira s.l. forests by conducting a comprehensive bibliographic survey of literature published from 2009 to 2021, complemented by unpublished data. We also provide insights into the ecological status of these forests and the stressors affecting them across the Mediterranean basin. Our results show that most Mediterranean coasts remain un(der)studied and that the available information is concentrated in spatially limited coastal areas, restricted to very few species. When the ecological status is reported, data is highly heterogeneous, making any comparisons problematic, what claims for the description and use of easy and standardized monitoring methods for comparative purposes. Drivers of decline of Cystoseira s.l. forest have been even less investigated and, therefore, still poorly characterized. Our results highlight that our current knowledge is still insufficient to implement effective conservation and restoration strategies at the basin scale but also regionally. We call for the urgent need for mapping and standardized monitoring of Cystoseira s.l. forests to obtain baseline information for future management strategies involving their conservation, the mitigation of the stressors threatening them and the restoration of the degraded forests.

Standardized protocol for reproductive phenology monitoring of fucalean algae of the genus Cystoseira s.l. with potential for restoration - Fabio Rindi; Alba Vergés; Irene Zuchegna; Silvia Bianchelli; Sònia de Caralt; Cristina Galobart; Jorge Santamaría; Francesco Martini; Margalida Monserrat; Sotiris Orfanidis; Cèlia Sitjà; Soultana Tsioli; et al. (Frontiers in Marine Science, 2023)
Active marine restoration is strongly encouraged to prevent the loss of the valuable habitats formed by Cystoseira sensu lato species, since they enhance biodiversity and preserve ecosystem functions and services. Current restoration interventions are mainly based on recruitment enhancement methods by deploying bags with fertile receptacles in situ or by outplanting juveniles grown ex situ under laboratory conditions. These methods allow the recovery of endangered species avoiding the depletion of the donor populations. In all cases, a priori knowledge of the reproductive phenology and recruitment periods of the species to be restored is essential, since the success of restoration techniques relies on collecting fertile branches and the obtention and survival of recruits. For their collection, identified donor populations characterized by dense Cystoseira s.l. cover should be studied. Specifically, monitoring the reproductive phenology of populations is crucial to detect the period of the year in which they develop mature reproductive structures and to understand how it might be linked to environmental conditions. Then, these general patterns on the reproductive phenology of Cystoseira s.l. species are essential to determine the most suitable time and conditions to plan for the most effective restoration action. Here, we provide a cost-effective and friendly protocol that can be easily and widely implemented for all Cystoseira s.l. species. We pose that this protocol provides a standardized and useful methodology to understand the environmental factors driving the optimal periods for sampling fertile branches across the Mediterranean Sea, and thus it can be an essential tool to plan future restoration actions.

Macroalgal forest restoration: the effect of the foundation species - Silvia Bianchelli; Simonetta Fraschetti; Francesco Martini; Marco Lo Martire; Ettore Nepote; Davide Ippoliti; Fabio Rindi; Roberto Danovaro (Frontiers in Marine Science, 2023)
Introduction Active restoration is the strategy needed to trigger or accelerate the recovery of degraded marine habitats, which provide the goods and services essential for preserving biodiversity and human wellbeing. Ecosystem engineers are generally the target species in the ecological restoration of marine ecosystems, and large-sized brown macroalgae (e.g., the Cystoseira complex) are a priority due to their crucial ecological importance and vulnerability in many regions of the Mediterranean Sea. Methods Here, we present the results of a successful intervention of ecological restoration of Gongolaria barbata . Results and Discussion One year after the restoration intervention, we observed the recovery of the canopy in terms of ca. 15m 2 with a significant increase in faunal abundance and biodiversity compared with reference areas. However, despite the high restored macroalgal growth rates, the assemblage structure was still significantly different from that of reference pristine areas. Despite the fast faunal colonization of a new 3D habitat linked to the successful re-introduction of the ecosystem engineers (i.e., macroalgae), the complete restoration of the properties of a habitat can be a much longer process. We conclude that, after 1 year, active restoration of macroalgal forests still results in a partial recovery of ecosystem functions (i.e., rehabilitation) rather than a full ecosystem restoration, thus stressing the need for long-term monitoring of restoration interventions.

A decision-support framework for the restoration of Cystoseira sensu lato forests - Christopher J. Smith; Jana Verdura; Nadia Papadopoulou; Simonetta Fraschetti; Emma Cebrian; Erika Fabbrizzi; Margalida Monserrat; Matilde Drake; Silvia Bianchelli; Roberto Danovaro; Dania Abdul Malak; Enric Ballesteros; et al. (Frontiers in Marine Science, 2023)
Macroalgal forests characterised by species of the genus Cystoseira sensu lato form important shallow coastal rocky habitats in the Mediterranean Sea. These forests support a high biodiversity and provide important ecosystem services and societal benefits. Currently these habitats are often in a poor condition in many areas, due to loss and degradation from both anthropogenic and climate stressors. Restoration has recently moved to the forefront of the United Nations and European Union agendas to reverse this trend, particularly in the last decade with the implementation of various international policies. However, this has been in the form of generic targets (e.g., restoration of 30% of degraded habitats by 2030) and has not been linked to specifically what habitat or species to restore, where and how. Initial targets have been missed, new targets are expected through the proposed EU Nature Restoration Law, but overall guidance is still lacking. There are few specific guides to marine habitat restoration limited to mostly seagrass, corals and shellfish. As a priority action for the recovery of coastal marine ecosystems a decision-support framework has been developed for the restoration of Mediterranean macroalgal forests, comprising a stepwise decision tree with additional descriptions of key elements to be considered for a restoration action. The decision tree includes steps concerning current and historical forest presence, site local condition assessment and choice of actions. Key considerations include restoration implementation (competence, society and support, finance and governance), success evaluation (at the target species and the ecosystem level) and long-term management. The framework builds on existing work on Cystoseira s.l. restoration, the work carried out in the EU AFRIMED project, but also on principles and guidelines in place for both generic and specific marine habitats. The work reported here has involved the expertise of scientists and information from stakeholders. Gaps were identified and recommendations were made, dealing with stressors, coordinating and networking stakeholders, integrating top down policy and bottom up initiatives, funding of restoration actions, establishing synergies between restoration, conservation and marine spatial planning and finally communication and publicity.

The challenge of setting restoration targets for macroalgal forests under climate changes - Erika Fabbrizzi; Sylvaine Giakoumi; Francesco De Leo; Laura Tamburello; Antonia Chiarore; Alberto Colletti; Marianna Coppola; Marco Munari; Luigi Musco; Fabio Rindi; Lucia Rizzo; Beatrice Savinelli; et al. (Journal of Environmental Management, 2023)

Marine heatwaves drive recurrent mass mortalities in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez‐Gras; Alba Medrano; Carlo Cerrano; Massimo Ponti; Robert Schlegel; Nathaniel Bensoussan; Eva Turicchia; Maria Sini; Vasilis Gerovasileiou; Nuria Teixido; Alice Mirasole; et al. (Global Change Biology, 2022)
Climate change is causing an increase in the frequency and intensity of marine heatwaves (MHWs) and mass mortality events (MMEs) of marine organisms are one of their main ecological impacts. Here, we show that during the 2015–2019 period, the Mediterranean Sea has experienced exceptional thermal conditions resulting in the onset of five consecutive years of widespread MMEs across the basin. These MMEs affected thousands of kilometers of coastline from the surface to 45 m, across a range of marine habitats and taxa (50 taxa across 8 phyla). Significant relationships were found between the incidence of MMEs and the heat exposure associated with MHWs observed both at the surface and across depths. Our findings reveal that the Mediterranean Sea is experiencing an acceleration of the ecological impacts of MHWs which poses an unprecedented threat to its ecosystems' health and functioning. Overall, we show that increasing the resolution of empirical observation is critical to enhancing our ability to more effectively understand and manage the consequences of climate change.

A Roadmap for the Restoration of Mediterranean Macroalgal Forests - Emma Cebrian; Laura Tamburello; Jana Verdura; Giuseppe Guarnieri; Alba Medrano; Cristina Linares; Bernat Hereu; Joaquim Garrabou; Carlo Cerrano; Cristina Galobart; Simonetta Fraschetti (Frontiers in Marine Science, 2021)
Canopy-forming macroalgae play a crucial role in coastal primary production and nutrient cycling, providing food, shelter, nurseries, and habitat for many vertebrate and invertebrate species. However, macroalgal forests are in decline in various places and natural recovery is almost impossible when populations become locally extinct. Hence, active restoration emerges as the most promising strategy to rebuild disappeared forests. In this regard, significant efforts have been made by several EU institutions to research new restoration tools for shallow and mesophotic reef habitats (e.g., MERCES EU project, AFRIMED, and ROCPOP-life) and effective techniques have subsequently been proposed to promote self-sustaining populations. Recent research indicates that macroalgal forest recovery requires a broad spectrum of measures, ranging from mitigating human impacts to restoring the most degraded populations and habitats, and that the viability of large restoration actions is compromised by ongoing human pressures (e.g., pollution, overgrazing, and climate change). We propose a roadmap for Mediterranean macroalgal restoration to assist researchers and stakeholders in decision-making, considering the most effective methods in terms of cost and cost-effectiveness, and taking background environmental conditions and potential threats into account. Last, the challenges currently faced by the restoration of rocky coastal ecosystems under changing climate conditions are also discussed.

Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Simonetta Fraschetti; Chris McOwen; Loredana Papa; Nadia Papadopoulou; Meri Bilan; Christoffer Boström; Pol Capdevila; Marina Carreiro-Silva; Laura Carugati; Emma Cebrian; Marta Coll; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.

Effects of Natural and Anthropogenic Stressors on Fucalean Brown Seaweeds Across Different Spatial Scales in the Mediterranean Sea - Sotiris Orfanidis; Fabio Rindi; Emma Cebrian; Simonetta Fraschetti; Ina Nasto; Ergun Taskin; Silvia Bianchelli; Vasileios Papathanasiou; Maria Kosmidou; Annalisa Caragnano; Soultana Tsioli; Stefano Ratti; et al. (Frontiers in Marine Science, 2021)
Algal habitat-forming forests composed of fucalean brown seaweeds ( Cystoseira , Ericaria , and Gongolaria ) have severely declined along the Mediterranean coasts, endangering the maintenance of essential ecosystem services. Numerous factors determine the loss of these assemblages and operate at different spatial scales, which must be identified to plan conservation and restoration actions. To explore the critical stressors (natural and anthropogenic) that may cause habitat degradation, we investigated (a) the patterns of variability of fucalean forests in percentage cover (abundance) at three spatial scales (location, forest, transect) by visual estimates and or photographic sampling to identify relevant spatial scales of variation, (b) the correlation between semi-quantitative anthropogenic stressors, individually or cumulatively (MA-LUSI index), including natural stressors (confinement, sea urchin grazing), and percentage cover of functional groups (perennial, semi-perennial) at forest spatial scale. The results showed that impacts from mariculture and urbanization seem to be the main stressors affecting habitat-forming species. In particular, while mariculture, urbanization, and cumulative anthropogenic stress negatively correlated with the percentage cover of perennial fucalean species, the same stressors were positively correlated with the percentage cover of the semi-perennial Cystoseira compressa and C. compressa subsp. pustulata . Our results indicate that human impacts can determine spatial patterns in these fragmented and heterogeneous marine habitats, thus stressing the need of carefully considering scale-dependent ecological processes to support conservation and restoration.

Ocean literacy and scientific data acquisition through citizen science campaigns: a mixed approach in the Maltese Islands to collect information on Pinna nobilis and Pinna rudis - ALAN DEIDUN; MONICA PREVIATI; ALESSIO MARRONE; ADAM GAUCI; AUDREY ZAMMIT; RAISA TARASOVA; ANTHONY GALEA; JOHANN GALDIES; SIMONETTA FRASCHETTI; ALDO DRAGO (Mediterranean Marine Science, 2021)
The genus Pinna includes two species in the Mediterranean Sea: Pinna nobilis and Pinna rudis. Both these species are under threat from multiple stressors. Pinna nobilis, in particular, has been exhibiting mass mortality events (MMEs) since 2016. The population and distribution of these species have never been comprehensively explored in the Maltese archipelago, and in this work, we collate information collected between 2006 and 2019 through a number of SCUBA underwater visual census monitoring programs. The logistical barriers surrounding SCUBA-based sampling techniques and the low-density distribution of these species constitute significant obstacles to an extensive conventional population assessment. Citizen science was thus also deployed in this study to supplement the data collected through SCUBA surveys: recreational SCUBA divers worked as citizen scientists, providing data on the distribution of these two endangered species from areas never explored before. This information can be used for assessing the conservation status of P. nobilis and P. rudis in Maltese waters, whilst contributing to the next generation of ocean-literate citizens.

Twelve Recommendations for Advancing Marine Conservation in European and Contiguous Seas - Stelios Katsanevakis; Marta Coll; Simonetta Fraschetti; Sylvaine Giakoumi; David Goldsborough; Vesna Mačić; Peter Mackelworth; Gil Rilov; Vanessa Stelzenmüller; Paolo G. Albano; Amanda E. Bates; Stanislao Bevilacqua; et al. (Frontiers in Marine Science, 2020)

Rhodolith Beds Heterogeneity along the Apulian Continental Shelf (Mediterranean Sea) - Giovanni Chimienti; Lucia Rizzo; Sara Kaleb; Annalisa Falace; Simonetta Fraschetti; Francesco De Giosa; Angelo Tursi; Enrico Barbone; Nicola Ungaro; Francesco Mastrototaro (Journal of Marine Science and Engineering, 2020)
Rhodolith beds represent a key habitat worldwide, from tropical to polar ecosystems. Despite this habitat is considered a hotspot of biodiversity, providing a suite of ecosystem goods and services, still scarce quantitative information is available thus far about rhodolith beds occurrence and ecological role, especially in the Mediterranean Sea. This study reports the composition and patterns of distribution of rhodolith assemblages found in four study areas along ca. 860 km of coast in the Central Mediterranean Sea. These rhodolith beds were studied for the first time and significant differences at all spatial scales have been highlighted, documenting the high variability of this habitat. Rhodolith species composition, morphology and distribution have been discussed considering the potential role of environmental factors in driving these patterns. The need for improving their protection is discussed to complement present conservation and management initiatives, particularly in the frame of the EU Marine Strategy Framework Directive.

Large-Scale Sea Urchin Culling Drives the Reduction of Subtidal Barren Grounds in the Mediterranean Sea - Giuseppe Guarnieri; Stanislao Bevilacqua; Neus Figueras; Laura Tamburello; Simonetta Fraschetti (Frontiers in Marine Science, 2020)

The Status of Coastal Benthic Ecosystems in the Mediterranean Sea: Evidence From Ecological Indicators - Stanislao Bevilacqua; Stelios Katsanevakis; Fiorenza Micheli; Enric Sala; Gil Rilov; Gianluca Sarà; Dania Abdul Malak; Ameer Abdulla; Vasilis Gerovasileiou; Elena Gissi; Antonios D. Mazaris; Carlo Pipitone; et al. (Frontiers in Marine Science, 2020)

Habitat Features and Their Influence on the Restoration Potential of Marine Habitats in Europe - Trine Bekkby; Nadia Papadopoulou; Dario Fiorentino; Chris J. McOwen; Eli Rinde; Christoffer Boström; Marina Carreiro-Silva; Cristina Linares; Guri Sogn Andersen; Elizabeth Grace Tunka Bengil; Meri Bilan; Emma Cebrian; et al. (Frontiers in Marine Science, 2020)

Modeling Macroalgal Forest Distribution at Mediterranean Scale: Present Status, Drivers of Changes and Insights for Conservation and Management - Erika Fabbrizzi; Michele Scardi; Enric Ballesteros; Lisandro Benedetti-Cecchi; Emma Cebrian; Giulia Ceccherelli; Francesco De Leo; Alan Deidun; Giuseppe Guarnieri; Annalisa Falace; Silvia Fraissinet; Chiara Giommi; et al. (Frontiers in Marine Science, 2020)

Collaborative Database to Track Mass Mortality Events in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez-Gras; Jean-Baptiste Ledoux; Cristina Linares; Nathaniel Bensoussan; Paula López-Sendino; Hocein Bazairi; Free Espinosa; Mohamed Ramdani; Samir Grimes; Mouloud Benabdi; Jamila Ben Souissi; et al. (Frontiers in Marine Science, 2019)

Light and Shade in Marine Conservation Across European and Contiguous Seas - Simonetta Fraschetti; Carlo Pipitone; Antonios D. Mazaris; Gil Rilov; Fabio Badalamenti; Stanislao Bevilacqua; Joachim Claudet; Hrvoje Carić; Karsten Dahl; Giovanni D’Anna; Darius Daunys; Matthew Frost; et al. (Frontiers in Marine Science, 2018)

A hazardous place to live: spatial and temporal patterns of species introduction in a hot spot of biological invasions - Giuseppe Guarnieri; Simonetta Fraschetti; Cesare Bogi; Bella Sarah Galil (Biological Invasions, 2017)

The alien species Caulerpa cylindracea and its associated bacteria in the Mediterranean Sea - Lucia Rizzo; Simonetta Fraschetti; Pietro Alifano; Graziano Pizzolante; Loredana Stabili (Marine Biology, 2016)

‘Double trouble’: the expansion of the Suez Canal and marine bioinvasions in the Mediterranean Sea - Bella S. Galil; Ferdinando Boero; Marnie L. Campbell; James T. Carlton; Elizabeth Cook; Simonetta Fraschetti; Stephan Gollasch; Chad L. Hewitt; Anders Jelmert; Enrique Macpherson; Agnese Marchini; Cynthia McKenzie; et al. (Biological Invasions, 2015)

Grazer removal and nutrient enrichment as recovery enhancers for overexploited rocky subtidal habitats - Giuseppe Guarnieri; Stanislao Bevilacqua; Fabio Vignes; Simonetta Fraschetti (Oecologia, 2014)

Global environmental changes: setting priorities for Latin American coastal habitats - Alexander Turra; Aldo Cróquer; Alvar Carranza; Andrés Mansilla; Arsenio J. Areces; Camilo Werlinger; Carlos Martínez‐Bayón; Cristina Aparecida Gomes Nassar; Estela Plastino; Evangelina Schwindt; Fabrizio Scarabino; Fungyi Chow; et al. (Global Change Biology, 2013)
As the effects of the Global Climate Changes on the costal regions of Central and South Americas advance, there is proportionally little research being made to understand such impacts. This commentary puts forward a series of propositions of strategies to improve performance of Central and South American science and policy making in order to cope with the future impacts of the Global Climate Changes in their coastal habitats.

Advancing marine conservation planning in the Mediterranean Sea - Sylvaine Giakoumi; Tessa Mazor; Simonetta Fraschetti; Salit Kark; Michelle Portman; Marta Coll; Jeroen Steenbeek; Hugh Possingham (Reviews in Fish Biology and Fisheries, 2012)

Increasing heterogeneity of sensitive assemblages as a consequence of human impact in submarine caves - Giuseppe Guarnieri; Antonio Terlizzi; Stanislao Bevilacqua; Simonetta Fraschetti (Marine Biology, 2012)

The use of taxonomic distinctness indices in assessing patterns of biodiversity in modular organisms - Stanislao Bevilacqua; Simonetta Fraschetti; Antonio Terlizzi; Ferdinando Boero (Marine Ecology, 2009)
Estimating diversity of modular organisms may be problematic due to actual difficulties in discriminating between ‘individuals’ and quantifying their abundances. Quantitative data, when available, are collected through methods that could preclude the application of classical diversity indices, making comparisons among studies difficult. Taxonomic distinctness indices, such as the ‘Average Taxonomic Distinctness’ (Δ + ) and the ‘Variation in Taxonomic Distinctness’ (Λ + ) may represent suitable tools in investigating diversity beyond the simple species number. The potential usefulness of such indices has been explored almost exclusively on unitary organisms, neglecting modular ones. In this study, we employed Δ + and Λ + to analyse patterns of diversity of epiphytic hydroid assemblages living on Cystoseira seaweeds at a hierarchy of spatial scales, along 800 km of rocky coast (SE Italy). ANOVA on species richness and Λ + showed no significant difference in sample diversity at the investigated spatial scales. In contrast, there were significant differences at the scale of 10s of km in Δ + . Analyses based on simulations detected significant variations at all spatial scales in Δ + . Such findings underline the potential of Δ + in highlighting relevant spatial scales of variation in patterns of hydroid diversity. Our results also suggest that the interplay between natural environmental variations and the complex ecological traits of modular organisms might affect taxonomic distinctness indices. We stress the need for further investigations focusing on modular organisms before any generalizations on the use of taxonomic relatedness measures in examining marine biodiversity can be made.

Local vs regional effects of substratum on early colonization stages of sessile assemblages - Giuseppe Guarnieri; Antonio Terlizzi; Stanislao Bevilacqua; Simonetta Fraschetti (Biofouling, 2009)

Trophic importance of subtidal metazoan meiofauna: evidence from in situ exclusion experiments on soft and rocky substrates - Roberto Danovaro; Mariaspina Scopa; Cristina Gambi; Simonetta Fraschetti (Marine Biology, 2007)

Effects of Desertification Caused by Lithophaga lithophaga (Mollusca) Fishery on Littoral Fish Assemblages along Rocky Coasts of Southeastern Italy - PAOLO GUIDETTI; SIMONETTA FRASCHETTI; ANTONIO TERLIZZI; FERDINANDO BOERO (Conservation Biology, 2004)
We surveyed shallow, rocky reefs in southwestern Apulia (Mediterranean Sea) to assess the effects on coastal fish assemblages of the date mussel ( Lithophaga lithophaga ) fishery, an illegal practice that strips the rocky reef bare. We visually sampled fish four times over 15 months at three locations, one affected by date‐mussel fishery and two controls. The fish assemblage at the affected location differed significantly from those at the control locations over all sampling times. Herbivorous fishes, sparids, and labrids (genus Symphodus ) contributed most to the differences between the affected location and controls. Lower densities of Symphodus spp. were observed at the affected location, whereas detritivorous fishes were recorded exclusively at control sites. Small serranids and sparids showed temporal trends that differed between the affected location and the control locations. Our results suggest that the date‐mussel fishery affects fish assemblages chiefly through reduction of arborescent macroalgae (contributing to habitat complexity and primary production) and emphasize the need for more effective policing against this destructive practice.

Marine Protected Areas in the Mediterranean Sea: Objectives, Effectiveness and Monitoring - Simonetta Fraschetti; Antonio Terlizzi; Fiorenza Micheli; Lisandro Benedetti‐Cecchi; Ferdinando Boero (Marine Ecology, 2002)
The number of Marine Protected Areas (MPAs) is continuously increasing worldwide because of the increasing recognition of the profound effects that humans can have on marine systems. A large body of literature deals with marine reserves and their potential as conservation and management tools. In several cases, empirical evidence demonstrated that reserves can harbour greater diversity, higher abundance, and larger organisms than unprotected areas. In most cases, however, reserve design and site selection involved little scientific justification, with no direct test of most of the mechanisms assumed to work in a marine reserve. Field investigations of subtidal marine reserves are generally confounded by intrinsic ecological differences between sites investigated inside and outside reserves, by a lack of site and reserve replication, or by the absence of information about the biota before reserve establishment. This is particularly true in the Mediterranean Sea. The aim of this paper is to show that, at least in the Mediterranean basin, the effectiveness of MPAs has been rarely demonstrated because of lack of appropriate sampling designs. An MPA can be considered as a zone subjected to human impact, presumably a positive one. As a consequence, we propose the use of experimental procedures generally utilised for detecting environmental impacts.